Os limites formais para a celebração do acordo de leniência (Lei 12.846/13) em face das garantias do particular - Rodrigues, Diogo Alencar de Azevedo (2016)
This paper presents a study on the recent Law 12.846/13, in particular on the institute's leniency agreement, seeking to establish a framework for the conclusion of such adjustments in view of the rights and guarantees established by the Constitution of the Federative Republic of Brazil in 1988. Initially, it approaches the intense changes promoted in the modern state and sanctioning rights in general, the question is, then, the existence of a common core between criminal law and the sanctioning administrative law. Search is finally propose solutions to maximize the effectiveness of the control system and sanction of Law 12.846/13, in view of the need to harmonize the Public Regulation of legal certainty and the constitutional rights of legal entities investigated, especially when she celebrates the leniency agreement.